Assessment and Management of Delirium in Older Adults in the Emergency Department: Literature Review to Inform Development of a Novel Clinical Protocol. (July 2015) - Rosen, Tony; Connors, Scott; Clark, Sunday; Halpern, Alexis; Stern, Michael E.; DeWald, Jennifer; Lachs, Mark S.; Flomenbaum, Neal
Abstract : Delirium occurs frequently in older patients in the emergency department (ED), is underrecognized, and has potentially serious consequences. Despite its seriousness, delirium is frequently missed by emergency providers, and patients with unrecognized delirium are often discharged from the ED. Even when it is appropriately recognized, managing delirium in older adults poses a significant challenge for ED providers. Geriatric delirium is typically caused by the interaction of multiple factors, including several that are commonly missed: pain, urinary retention, constipation, dehydration, and polypharmacy. Appropriate management includes nonpharmacological management with medication intervention reserved for emergencies. We have developed a new, comprehensive, evidence-based protocol for diagnosis/recognition, management, and disposition of geriatric delirium patients in the ED with a focus on identifying and treating commonly missed contributing causes.